Reuse of MSWI bottom ash mixed with natural sodium bentonite as landfill cover material. Issue 6 (June 2013) - Puma, Sara; Marchese, Franco; Dominijanni, Andrea; Manassero, Mario
The research described in this study had the aim of evaluating the reuse of incinerator slag, mixed with sodium bentonite, for landfill capping system components. A characterization was performed on pure bottom ash (BA) samples from an incinerator in the north of Italy. The results show that the BA samples had appropriate properties as covers. The compacted dry unit weight of the studied BA (16.2 kN m −3 ) was lower than the average value that characterizes most conventional fill materials and this can be considered advantageous for landfill cover systems, since the fill has to be placed on low bearing capacity ground or where long-term settlement is possible. Moreover, direct shear tests showed a friction angle of 43°, corresponding to excellent mechanical characteristics that can be considered an advantage against failure. The hydraulic conductivity tests indicated a steady-state value of 8 × 10 −10 m s −1 for a mixture characterized by a bentonite content by weight of 10%, which was a factor 10 better than required by Italian legislation on landfill covers. The results from a swell index test indicated that fine bentonite swelled, even when divalent cations were released by the BA. The leaching behaviour of the mixture did not show any contamination issues and was far better than obtained for the pure BA. Thus, the BA–bentonite mixture qualified as a suitable material for landfill cover in Italy. Moreover, owing to the low release of toxic compounds, the proposed cover system would have no effect on the leachate quality in the landfill.